Anti-Apoptotic Effect of Synthetic Leu-Enkephalin Dalargin on Rat Leukocytes in Cold Stress Model in Vivo - Shcheniavsky, Ivan (Problems of Cryobiology and Cryomedicine, 2021)
In this research, a protective effect of synthetic analogue of leu-enkephalin dalargin on peripheral blood leukocytes of cold stress-exposed homeotherms has been investigated. The impact of this peptide and in vivo cold stress on cell composition of leukoconcentrate, leukocyte viability and DNA fragmentation degree in rat leukocytes, has been studied by using confocal microscopy. A decreased relative count of lymphocytes and an increased neutrophil one were established as significantly less pronounced in the animals injected with dalargin before cooling, than in non-handled ones. The dalargin administration was also shown to enhance the viability of peripheral blood leukocytes in rats exposed to cold stress. Preliminary administration of dalargin to animals significantly reduced both the degree of DNA fragmentation and a relative count of leukocytes with fragmented DNA in peripheral blood. Simultaneous introduction of opioid receptor antagonist naloxone to animals eliminated a protective effect of opioid receptor agonist dalargin. Our findings demonstrated the opioid receptor-mediated antiapoptotic effect of dalargin on peripheral blood leukocytes under in vivo cold stress. Probl Cryobiol Cryomed 2021; 31(1): 003–013